Engaging communities towards restoring hillslope seep wetlands in the Tsitsa River catchment of South Africa. (September 2022) - Libala, Notiswa; Odume, Oghenekaro Nelson; Palmer, Carolyn G.
Abstract: Considering the increase of wetland degradation globally, a need exists for an integrated approach that involves communities to collectively protect and sustain wetlands. In the Tsitsa River catchment, South Africa, hillslope seep wetlands are among the vulnerable wetland ecosystems with potential to trigger erosion in the landscape. This study engaged with livestock owners in communities to elicit information regarding their knowledge of hillslope seep wetlands, and their understanding of the importance of these wetlands. Using purposive sampling, researchers interviewed 31 livestock owners and analysed the data using thematic analysis. Results revealed that communities largely perceived hillslope seep wetlands as important ecosystems for their livelihoods. They recognized that the importance stems from services provided by these wetlands. Although the communities viewed hillslope seep wetlands as important ecosystems for livelihoods, however, they also perceived them as highly eroded ecosystems. Community members indicated willingness to strengthen local natural resource governance systems, which could lead to better management or restoration of hillslope seep wetlands. Protective strategies for hillslope seep suggested included fencing, active herding and rotational grazing. This study provides one example from South Africa demonstrating the importance of active involvement of local communities toward successful management of natural resources.